Comparing the Determinants of Western and Chinese Commercial Ties with Africa - David G. Landry (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2019)
Many have hypothesized that Chinese firms undermine the global drive to promote good governance in developing countries, and in Africa in particular, by targeting poorly governed countries for commercial ventures. This paper by David G. Landry tests that hypothesis. It is the first to explicitly compare the determinants of Chinese and Western commercial activities through quantitative modeling and finds that governance quality among African countries plays a positive role in predicting their commercial activity, in terms of their foreign direct investment inflows, exports, and imports—with both Western countries and China.
Keywords: 330